Factors Influencing Investors’ Adoption of Robo-Advisors in Bangalore: An Extrapolation from the Fiduciary Duty of Investment Advisors (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Robo-advisors are one of the prominent fintech innovations seen in the era of digitization. This study intended to investigate the factors that influence robo-advisor adoption among investors in Bangalore, India. It integrates the principles of Fiduciary Duty (Care and Loyalty) with the Technology Acceptance Model (TAM). From the analysis of 301 valid responses, the research found that while all fiduciary drivers are significant, Firm Reputation acts as the strongest predictor of value, and Privacy Protection is the primary driver of trust. Interestingly, investment experience did not moderate the relationship between trust and adoption, which suggests that there is a universal trust threshold across all investor segments in the Bangalore market.